Perancangan Produk Inovatif Alat Bantu Pencekam Kelapa untuk Proses Pembelahan - Muhammad Nur; Usman Usman; Azwinur Azwinur (Jurnal Teknologi, 2022)
The coconut splitting process carried out by Indonesian generally is still using the conventional method, without using tools to grip the coconut. So, it will be at high risk during the coconut splitting process. If an accident occurs, of course it will take a long time for the healing process. Therefore, a new innovation here is needed by designing a coconut splitting tool for the conventional splitting process. The specifications of the tool are planned to be able to withstand a load of 19.62N (2 kg) with a splitting depth of 68mm. For this clamping tool, the material used is ST37. This material was selected because it is easy to obtain, the price is affordable, and the quality is sufficient for such a tool.